Poverty Reduction Strategies : Their Importance for Disability - World Bank (Washington, DC, 2013)
This report is an attempt to assess the validity of poverty reduction strategies as an effective tool to manage poverty brought about by disability, by reviewing the disability policy content of poverty reduction strategy papers. In doing so, the report focuses on whether the specific poverty dimensions of disabled persons are acknowledged and the critical interventions for improving the economic and social integration of disabled persons are included in poverty reduction strategy papers. There is a wide consensus that disabled persons, being disproportionately poor, are among the population groups that should benefit from the poverty reduction programs of poverty reduction strategy papers. The issue, however, is whether they are de facto excluded from benefiting from current poverty reduction strategies. Poverty reduction strategy papers do not meet the needs of disabled persons because they are based on a limited social protection policy that conveys a wrong impression about the abilities and aspirations of the majority of disabled persons. Furthermore, they do not reflect the basic principles of the modern approach to disability adopted by the United Nations. Progress across regions and in developing the various components of the disability strategy has remained uneven. Partly for historical and institutional reasons related to the importance of pensions and transfers for the government budget, disability issues have received more attention among Eastern European countries. They have received the least attention in the Africa region.